Global Perspectives on Pharmaceutical Tracking and Traceability Systems: A Review of Logistics Technologies in Healthcare - Nursyabila, Ardelia; Jamal, Siti Aisyah; Haviana, Evan; Hardi, Yuni (Public Health and Safety International Journal, 2025)
The pharmaceutical supply chain faces increasing pressure to ensure transparency, safety, and efficiency across global operations. This study presents a systematic literature review (SLR) of global tracking and traceability systems in pharmaceutical logistics, focusing on technological innovations such as RFID, barcoding, and blockchain. A total of six peer-reviewed articles were selected based on inclusion criteria through the PRISMA methodology. The results highlight the growing adoption of traceability systems in developed countries driven by regulatory frameworks such as the DSCSA (USA) and FMD (EU). Technologies such as blockchain show high potential in improving drug authentication and preventing counterfeiting. However, barriers such as high implementation costs, lack of infrastructure, and limited standardization continue to hinder adoption in developing nations. The study concludes that pharmaceutical traceability is a strategic necessity for public health and requires coordinated efforts between governments, industries, and global organizations.